COMMUNICATION GAP ANALYSIS AT AEROSPACE MANUFACTURING COMPANY - MOHAMAD, EFFENDI; Abdullah, Rohana; Wan Mahmood, Wan Hasrulnizzam (Penerbit Universiti Teknikal Malaysia Melaka, 2008)
The objective of this research is to investigate the communication gap at the Aerospace Manufacturing Company by using semi-structure interview and focus group discussion technique. A standard report is also produced to overcome this communication issues by having each person in each level to review and report their standard operation to their subordinates regularly based on the decided frequency.